Development of scientific and methodological approach to quantitative and qualitative assessment of intellectual property management in industrial enterprises - Raiko, Diana; Cherepanova, Viktoriia; Sylka, Ihor; Podrez, Olha; Fedorenko, Irina (Eastern-European Journal of Enterprise Technologies, 2021)
The competitiveness, market value and income of an enterprise depend on the level of intellectual property management. Therefore, the aim of research is to develop, substantiate and test a scientific and methodological approach to a quantitative and qualitative assessment of the management of intellectual property of industrial enterprises. The originality of the proposed approach is that on the basis of the concept of "management of intellectual property" a procedure for current management has been developed, the main stage of which is a quantitative and qualitative assessment. The assessment is based on the structural and logical model, which is built according to two criteria. The criteria make it possible to determine the current state of the use of intellectual property (intangible assets) – a quantitative assessment, and the prospect of further use (intellectual potential) – a qualitative assessment. A quantitative assessment involves the calculation of indicators characterizing the state of assets, the dynamics of the impact on the market value of the enterprise, the profitability of production, which is proposed to be determined through the net cash flow from operating activities. A qualitative assessment is carried out in terms of components (information and investment, organizational and legal, economic, personnel and motivation), tools and relative indicators that characterize the intellectual potential of an industrial enterprise. The assessment is carried out using a general integral indicator, which is of practical importance, since it shows the existing level of intellectual property management and directions for improvement in the future. The approbation of the scientific and methodological approach was carried out on the example of three Ukrainian coke-chemical enterprises (CJSC Avdeevka Coke Plant, CJSC Zaporozhkoks, CJSC Yuzhkoks) of the American association SUNCOKE ENERGY, INC and the Polish association J.S.W. S.A. Group. Empirical studies for the period from 2015 to 2019 made it possible to build a scale for assessing the level of intellectual property management according to the Harrington function